Hyblaea : studi di archeologia e topografia dell'altopiano ibleo. - Cannata, Antonino; Cugno, Santino Alessandro; Scaravilli, Marco Stefano (Access archaeology., 2022)
A collection of ten papers focusing on the prehistoric, late-ancient and medieval-historical archaeological heritage of the Hyblaean area and in the south-eastern apex of Sicily, with particular attention to rupestrian archaeology.